Impact of alkoxy chain length on carbazole-based, visible light-driven, dye sensitized photocatalytic hydrogen production. Issue 43 (30th September 2015) - Watanabe, Motonori; Hagiwara, Hidehisa; Ogata, Yudai; Staykov, Aleksandar; Bishop, Sean R.; Perry, Nicola H.; Chang, Yuan Jay; Ida, Shintaro; Tanaka, Keiji; Ishihara, Tatsumi
Abstract : Alkoxyphenyl-substituted carbazole-based metal-free organic dyes were synthesized and effectively used for dye-sensitized, visible-light-driven, photocatalytic hydrogen production. Abstract : Alkoxyphenyl-substituted carbazole-based metal-free organic dyes were synthesized and effectively used for dye-sensitized, visible-light-driven, photocatalytic hydrogen production. Photocatalytic hydrogen production was investigated using a TiO2 /dye/Pt structure with triethanolamine as the sacrificial reagent. The dye-loaded TiO2 photocatalyst exhibited a high yield of hydrogen production when the length of the alkoxy chain was long enough to sufficiently improve the hydrophobicity at the interface between the dye-loaded TiO2 and the water medium. In the alkoxyphenyl-substituted carbazole dyes, the dye with the longest alkoxy chain (C22 ) exhibited the best hydrogen production performance, but it had a yield only slightly better than that of the dye with the second longest chain length (C16 ). The dyeC22 displayed a turnover number (TON) of 3094 after 24 h of visible light irradiation (>420 nm). However, the compound with no hydrophobic substituent (C1 ), exhibited the lowest hydrogen production performance with a TON of 1497. Thus, a 207% increase in the hydrogen production yield was observed when hydrophobic substituents were present. Analysis of time-resolved absorption spectra, impedance spectra and incident photon conversion efficiency spectra revealed that the alkoxy chain has a hydrophobic effect at the interface between the dye-loaded TiO2 and the water. Specifically, the hydrophobicity of the dye improved the charge-recombination lifetime for electron injection from the dye into the TiO2 surface in the water for hydrogen production.